2020
DOI: 10.1097/md.0000000000019600
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the whole pelvic morphology in slipped capital femoral epiphysis

Abstract: Slipped capital femoral epiphysis (SCFE) is a very common disorder affecting the adolescent hip. The etiology of SCFE is multifactorial and mechanical force associated with the characteristic morphology of the hip is considered one of the causes of SCFE. We investigated the characteristics of whole pelvic morphology including pelvic incidence (PI) in patients with SCFE and compared it with pelvic morphology in healthy children. We retrospectively assessed the whole pelvic morphology of 17 patients with SCFE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The epiphysis moves posteriorly and medially in relation to the metaphysis as a result of a weak proximal femoral physis (13) . Increased physeal obliquity, post-radiation pelvic treatment and endocrinopathy such as hypothyroidism, hypogonadism and hypopituitarism, obesity as well as increased femoral retroversion, are all implicated in the SCFE (14) .…”
Section: Discussionmentioning
confidence: 99%
“…The epiphysis moves posteriorly and medially in relation to the metaphysis as a result of a weak proximal femoral physis (13) . Increased physeal obliquity, post-radiation pelvic treatment and endocrinopathy such as hypothyroidism, hypogonadism and hypopituitarism, obesity as well as increased femoral retroversion, are all implicated in the SCFE (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this method is fundamentally limited by the use of a 2D image to represent a complex 3D structure by the use of manual US probes. These characteristics may be dependent on the radiologist's experience and can result in subjective measurements of Graf's alpha and beta angles, subsequently increasing the risk of poor inter-and intra-observer agreement [3][4][5][6][7]. Several researchers have attempted to compensate for these limitations using 3D US or automatically corrected US images to evaluate DDH [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that the Graf method has low inter-and intra-observer agreement because it is highly dependent on the ability of the examiner [3][4][5][6][7]. If the exact location of the standard plane in the pelvis is identified, it may contribute to improving the accuracy of the Graf method.…”
Section: Introductionmentioning
confidence: 99%
“…Simple AP and Frog leg lateral views are adequate in assessing the slip. However, in acute presentation, wherein hip abduction is not possible to obtain the frog-leg lateral view, a CT scan of the pelvis comes to the rescue [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%